Liberalization of the European Union Rail Transport Markets: Challenges and Solutions - Nikitinas, Vilius (Teisė, 2024)
The processes of liberalization of railway transport markets in the European Union started at the end of the 20th century. The Member States of the European Union were encouraged to open the railway transport markets and create conditions for private carriers to compete with the state operators established in the market. Although the processes of liberalization of railway transport markets have been going on for several decades, the topic is still relevant for Lithuania, since in the Lithuanian railway transport market railway transport services, i.e. cargo and passenger transportation services, are provided only by national carriers. This means that railway transport services in Lithuania are basically concentrated in the hands of state carriers, while private operators currently do not provide services in this market. Annual studies by the European Commission show that Lithuania remains one of the last Member States of the European Union with a closed railway transport market. For this reason, it is relevant to examine what problems other Member States faced when opening their railway transport markets, and what can be learned from these problems in Lithuania. The author of the article, examining the practice of the Court of Justice of the European Union, found that the main factors hindering the liberalization processes are the inappropriate separation of public railway infrastructure management and transport service activities, and inappropriate implementation of the principles of capacity allocation and charging. In the opinion of the author of this article, the implementation of liberalization processes in the markets of Member States can be ensured by properly adapted legal regulation that meets the needs of the relevant market, proper implementation of railway management model chosen by the Member State, and a strong role of the regulatory body.
Keywords: railway transport; liberalization; non-discriminatory access; competition